The villainess turns the hourglass. 3 - SANSOBEE (Comics author) (Ize Press, 2024)
Amid the despair caused by Oscar's rejection, Aria uncovers the truth behind his and Mielle's relationship -- his sister, Lady Isys, has been pulling the strings to bring them together! This means Aria has no time to wallow in self-doubt. She needs power that can rival the dukedom...and is wealth not the greatest power of all? Meanwhile, Aria receives a tempting invitation to an exclusive gathering from Lord Asher, whose intentions remain suspicious at best. It's hard to tell whether he's a friend or foe--but if Aria wants to survive, she's going to have to take a gamble!